Pengawasan Pemerintah Terhadap Pengusaha Yang Memberhentikan Pekerja Wanita Hamil - Fataruba, Firta Risky; Rugebregt, Revency Vania; Tita, Heillen Martha Yosephine (Faculty of Law Universitas Pattimura, 2025)
Currently, employment issues are still in the spotlight. Lack of guarantees for safety, health and reproductive rights for female workers is one of the factors causing various problems in the employment sector. Workers as workers in companies still receive discriminatory treatment from employers, this means that the rights that female workers should receive, such as protection for the safety of pregnant women, health and reproductive rights of female workers, are not fully provided. The research method used is normative juridical which uses a statutory approach and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials. The results of this research emphasize that there should be stricter sanctions for every violation of labor practices carried out by companies, so that legal protection for the safety, health and reproductive rights of pregnant female workers and the obstacles faced in implementing protection for the safety, health and reproductive rights of female workers Government Supervision, Entrepreneurs, Pregnant Women Workers.